Girls under pressure - Wilson, Jacqueline (New York : Delacorte Press, 2002)
Ellie learns to deal with her self-image as she battles anorexia.
First published: Great Britain : Doubleday, 1998.
Booklist.
Bulletin (Center for Children's books).
Wilson's Junior High School.
5.2.
5.2
Keywords: Anorexia nervosa -- Fiction; Weight control -- Fiction; Anorexia nervosa -- Fiction; Weight control -- Fiction